Potential Utility of 123I-MIBG Scintigraphy as a Predictor of Falls in Parkinson's Disease - Murakami, Nagahisa; Sako, Wataru; Haji, Shotaro; Furukawa, Takahiro; Otomi, Yoichi; Otsuka, Hideki; Izumi, Yuishin; Harada, Masafumi; Kaji, Ryuji (Frontiers in Neurology, 2019)
Background: Falls are associated with poor prognosis in patients with Parkinson’s disease (PD). Although several factors related to falls were reported in patients with PD, objective predictors of falls are not identified. We aimed to determine whether 123I-meta-iodobenzylguanidine (MIBG) cardiac scintigraphy could be a useful biomarker to predict falls. Methods: Forty-five patients with PD were enrolled in this study. These subjects were followed up more than 5 years after MIBG scintigraphy and were divided into two groups: one with decreased uptake of MIBG and the other without decreased uptake of MIBG. The cut-off value for the delayed heart-to-mediastinum ratio was 1.8. Kaplan-Meier analysis and a log-rank test were performed to test the predictive power of MIBG cardiac scintigraphy for falls. Univariate analysis was selected because we did not have appropriate data for adjustment, such as motor and cognitive assessment. Results: The group with decreased uptake of MIBG had a significantly higher incidence of falls than that without decreased uptake of MIBG (P = 0.022, log-rank test). Conclusions: Although the limitations of this study were lack of several key factors including motor and cognitive assessment, MIBG cardiac scintigraphy may be used to predict falls in patients with PD.